The Inﬂuence of Politicians on Television Content in Post-Authoritarian Indonesia - Morissan Morissan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
The downfall of the last authoritarian ruler in May 1998 marked the beginning of the transition to democracy in Indonesia. Before 1998, the autocratic government ﬁrmly monitored media content for decades. With the current broadcast liberalization, Indonesian televisions can produce almost any kind of program contents. However, a question arises, who actually controls television content in the era of liberalization? How do political and economic factors inﬂuence television workers in shaping content? This empirical research intends to focus on the inﬂuence politicians have on television program content in four elections in post-authoritarian Indonesia. The research question is: how do politicians inﬂuence television workers in shaping their content? The question needs a qualitative descriptive answer from various sources, including interviews with around 100 television workers in the 10 largest TV stations, participant observations, documents, television reports, and other data sources. Research ﬁndings reveal that the relationship between politicians and television intensiﬁed ahead and during political campaigns. Most television stations had conducted a relatively fair and nonpartisan coverage of the 2004 and 2009 election, but unfair and partisan in the 1999 and 2014 elections.